Ultrasound-guided needle aspiration of parotid abscess - Takahashi, André (2012)
Ultrasound (US) has been used as a tool for parotid abscess diagnosis and treatment. The present article aimed to report a case of 72-year-old woman with parotid abscess treated by US-guided needle aspiration and conventional surgical drainage. Along with the clinical report, indications, advantages, and limitations of the method are discussed.